A Brief Study on the k-Dimensional Repunit Sequence - Eudes A. Costa; Paula M. M. C. Catarino; Paulo J. M. Vasco; Francisco R. V. Alves (Axioms)
In this paper, we aim to introduce and investigate the bidimensional, tridimensional and k-dimensional extension of Repunit numbers, with a particular focus on their recurrence relations, key properties, and various sum identities.